Designing a co‐productive study to overcome known methodological challenges in organ donation research with bereaved family members. (6th May 2019) - Noyes, Jane; Mclaughlin, Leah; Morgan, Karen; Roberts, Abigail; Stephens, Michael; Bourne, Janette; Houlston, Michael; Houlston, Jessica; Thomas, Sarah; Rhys, Revd Gethin; Moss, Bethan; Duncalf, Sue; et al.
Abstract: Background: Co‐production of research into public health services has yet to demonstrate tangible benefits. Few studies have reported the impact of co‐production on research outcomes. The previous studies of organ donation have identified challenges in engaging with public organizations responsible, gaining ethical approval for sensitive studies with the recently bereaved and difficulty in recruiting bereaved family members who were approached about organ donation. Objective: To address these challenges, we designed the first large co‐productive observational study to evaluate implementation of a new system of organ donation in Wales. This paper outlines the co‐productive strategies that were designed to overcome known methodological challenges and reports what impact they had on resolving these challenges. Design: Two‐year co‐produced study with multiple stakeholders with the specific intention of maximizing engagement with the National Health Service arm in Wales responsible for organ donation, and recruitment of bereaved family members whose perspectives are essential but commonly absent from studies. Setting and participants: NHS Blood and Transplant, Welsh Government and multiple patient and public representatives who served as co‐productive partners with the research team. Results: Co‐productive strategies enabled a smooth passage through four different ethics processes within the 10‐week time frame, family member recruitment targets to be surpassed, sharing of routinely collected data on 100% of potential organ donor cases and development of further research capacity and capability in a critically under researched area. Discussion and conclusion: Although expensive and time consuming, co‐production was effective and added value to research processes and study outcomes.